Elaboración y comprobación de la eficacia in vivo de crema humectante con extracto de tomate (Lycopersicum esculentum, Solanáceae) y arazá (Eugenia stipitata, Myrtáceae) - Villacís Vargas, Carmen Elizabeth (2014)
This study's main objective was to check the effectiveness of a cosmetic cream made with aqueous extracts of tomato and arazá. The effectiveness of the cream on 40 volunteers men and women, aged between 20 and 65 years was determined through a technique called corneometry skin bioengineering,. The aqueous extracts of arazá and tomato were prepared at a concentration of 90% color, odor and appearance, organoleptic tests were performed, also physical tests: pH and density with the extracts. Extracts were used immediately in the formula at a concentration of 7 and 3% respectively, and the organoleptic, physical and microbiological properties of the formulation were evaluated.